Identification and quantification of carotenoids, by HPLC-PDA-MS/MS, from Amazonian fruits - de Rosso, Veridiana V; Mercadante, Adriana Z (Journal of agricultural and food chemistry, 2007)
The major and minor carotenoids from six fruits, buriti (Mauritia vinifera), mamey (Mammea americana), marimari (Geoffrola striata), peach palm (Bactrys gasipaes), physalis (Physalis angulata), and tucuma (Astrocaryum aculeatum), all native to the Amazonia region, were determined by high-performance liquid chromatography-photodiode array detector-mass spectrometry detector (HPLC-PDA-MS/MS), fulfilling the recommended criteria for identification. A total of 60 different carotenoids were separated on a C30 column, all-trans-beta-carotene being the major carotenoid found in all fruits. The presence of apo-10'-beta-carotenol, found in mamey, was not previously reported in foods. In addition, this is the first time that the identification of beta-zeacarotene in natural sources is supported by MS data. The total carotenoid content ranged from 38 microg/g in marimari to 514 microg/g in buriti. All fruits analyzed can be considered good sources of provitamin A, especially buriti, with 7280 RE/100 g.